Flow and transport through unsaturated fractured rock - Evans, Daniel D.; Nicholson, Thomas J.; American Geophysical Union; University of Arizona; U.S. Nuclear Regulatory Commission; Sandia National Laboratories (Washington, DC : American Geophysical Union, 1987)
07